Analisis Faktor Resiko Hipertensi Pada Pra Lansia Di UPTD Puskesmas Lolomatua Kabupaten Nias Selatan - Januariana, Neni Ekowati; Lestari, Wanda; Nababan, Agnes Sry Vera; Giawa, Kristina Desimawati (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Hypertension is a global health issue that contributes to increased morbidity and mortality from cardiovascular diseases. The pre-elderly population requires special attention as they undergo a transitional phase toward old age, during which physiological changes increase the risk of hypertension. This study aims to identify risk factors for hypertension among pre-elderly individuals in the working area of UPTD Puskesmas Lolomatua, South Nias Regency. The study employs an analytical observational method with a case-control design, analyzing data using the Chi-Square test, Odds Ratio (OR), and 95% Confidence Intervals (CI). The study sample consists of 86 pre-elderly respondents, including 43 cases (hypertension) and 43 controls (non-hypertension). The results indicate a significant association between sodium intake and hypertension (p = 0.005; OR = 3.894), sleep quality (p = 0.000; OR = 4.350), and physical activity (p = 0.001; OR = 4.350). However, smoking habits were not associated with hypertension (p = 0.514; OR = 9.431). Pre-elderly individuals with excessive sodium intake, poor sleep quality, and low physical activity have a fourfold increased risk of developing hypertension. In contrast, smoking habits did not show a significant risk for hypertension. Therefore, regular health check-ups are recommended for pre-elderly individuals to maintain stable blood pressure.